Showcasing the Internationally Prioritized Medicinal Plants to Counteract the Pandemics – Potential Remedies for COVID-19 and other Forms of SARS: Internationally Prioritized Medicinal Plants to Counteract the COVID-19 - Khan, Shujaul Mulk; Abdullah; Rehman, Khadija; Ijaz, Ujala; Ali, Shahab; Jehangir, Sadia; Rehman, Amjad Ur; Shehzadi, Sara; Ahmad, Zeeshan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Indigenous communities throughout the globe respond to COVID-19 by their traditional medicinal systems as primary health care. Our lab was part of an international study that discusses the outcomes of a rapid response, preliminary survey during the first phase of the pandemic among social and community contacts in five metropolises heavily affected by the COVID-19 health crisis (Wuhan, Milan, Madrid, New York, and Rio de Janeiro) and in twelve rural areas or countries initially less affected by the pandemic (Appalachia, Jamaica, Bolivia, Romania, Belarus, Lithuania, Poland, Georgia, Turkey, Pakistan, Cambodia, and South Africa). Primarily, people have relied on teas and spices (“food-medicines”) to prevent and mitigate its symptoms. Urban diasporas and rural households seem to have repurposed homemade plant-based remedies that they use on daily basis to treat the flu and other respiratory problems and hence consider among the healthy foods. The most remarkable shift in many areas has been increased in the consumption of ginger and garlic, followed by onion, turmeric, lemon, chamomile, black tea, nettle, chili pepper, and apple. This study serves as a baseline for future systematic ethnobotanical studies countering COVID-19 and other vicious types of viruses. It aims to inspire in-depth research on how use patterns of plant-based foods and beverages, both “traditional” and “new,” are changing during and after the COVID-19 pandemic. Our reflections in this study call attention to the importance of ethnobiology, ethnomedicine, and ethno-gastronomy research into domestic health care strategies for improving community health. Some of these economically important plants are suggested to be extensively analyzed experimentally, for active ingredients, phytochemicals, and the precursor of vaccines and probable remedy of SARS including COVID-19.